2013
DOI: 10.1097/qad.0b013e32835ab1f2
|View full text |Cite
|
Sign up to set email alerts
|

Associations of human leukocyte antigen-G with resistance and susceptibility to HIV-1 infection in the Pumwani sex worker cohort

Abstract: Our study showed that specific HLA-G alleles are associated with resistance or susceptibility to HIV-1 acquisition in this high-risk population. Further studies are needed to understand its functional significance in HIV-1 transmission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 92 publications
(85 reference statements)
0
6
2
1
Order By: Relevance
“…In one study G*01:01:01 was significantly enriched in HIV-1 resistant sex workers, whereas G*01:04:04 was significantly associated with susceptibility to HIV-1 infection (Turk et al, 2013). However in Zimbabwean women, G*01:01:08 was associated with an increased risk of HIV-1 infection, while G*01:05N offered protection from heterosexual HIV-1 infection (Matte et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In one study G*01:01:01 was significantly enriched in HIV-1 resistant sex workers, whereas G*01:04:04 was significantly associated with susceptibility to HIV-1 infection (Turk et al, 2013). However in Zimbabwean women, G*01:01:08 was associated with an increased risk of HIV-1 infection, while G*01:05N offered protection from heterosexual HIV-1 infection (Matte et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Exons 2, 3 and 4 of HLA-G were amplified and sequenced using previously published primers (Turk et al, 2013, Hviid et al, 1997). Briefly, a 994-bp fragment encompassing exons 2 and 3 was amplified using primers HLAG_2/3PCRF (5’-CGGCCCCTGCGCGGAGGAGGGAGGGG-3’) and HLAG_2/3PCRR (5’-TCAGGACCAGAGGGAGGGCGATATTC-3’); primers HLAG_4PCRF (5’-AGGTGCTG-CTGGAGTGTC-3’) and HLAG_4PCRR (5’-TCTGGGAAAGGAGGTGAAG-3’) were used to amplify a 463-bp fragment spanning exon 4 (Turk et al, 2013). Thermocycling conditions were: 94°C for 2 min followed by 35 cycles of 94°C for 30 sec, 61.5°C/60°C for 30 sec (for exons 2-3 and exon 4, respectively) and 72°C for 1 min followed by a final extension step of 72°C for 7 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HLA-G*01:05N increases in HIV infection, which may be due to lack of HLA-G1 and HLA-G5 expression resulting in compensation by other HLA-G isoforms, which then may inhibit NK cell activation (263). It has also been shown that the HLA-G*01:01:01 genotype is significantly enriched in HIV-resistant women, while HLA-G*01:04:04 is associated with increased rates of seroconversion (264). …”
Section: The Complex Role Of Hla-g In Immunomodulationmentioning
confidence: 99%